Assessing the causal association of trauma with subsequent psychiatric disorders by a Mendelian randomization study trauma and common psychiatric disorders - Gu, Dongqing; Ou, Shan; Liu, Guodong (Frontiers in Psychiatry, 2023)
Objective: Trauma has been proposed as a risk factor for the development of psychiatric disorders. This study aimed to determine the causal role of trauma in six common psychiatric disorders.We obtained summary-level data for genetic variants associated with trauma and the corresponding association with psychiatric disorders from previous genome-wide association studies. Two-sample Mendelian randomization analyses were performed to estimate the causal association between trauma and psychiatric disorders, with inverse variance weighted used as the main method.Results: Genetically predisposed trauma was associated with an increased risk of psychiatric disorders [odds ratio (OR) =1.24, 95%, confidence interval (CI), 1.09 -1.40], anxiety disorder (OR=1.30, 95% CI, 1.10 -1.52) and schizophrenia (OR=1.48, 95% CI, 1.18 -1.84). However, the associations between trauma and sleep disorder (OR=1.17, 95% CI, 1.01 -1.35), as well as depression (OR=1.09, 95% CI, 1.02 -1.16) did not reach a Bonferroni corrected significance level. Besides, no association was observed between trauma and risk of bipolar disorder (OR=1.21, 95% CI, 0.98 -1.48) and eating disorder (OR=1.28, 95% CI, 0.88 -1.86).Trauma might be causally associated with an increased risk of some common psychiatric disorders such as anxiety disorder and schizophrenia. However, little evidence supported an association between trauma and risk of depression, bipolar disorder, sleep disorder, and eating disorder. Our findings offered novel insights into the trauma-mediated development mechanism of psychiatric disorders, and psychological intervention to patients with trauma may be an effective prevention strategy for psychological diseases.